The Regulation Contribution in Favor of the OEFA Under Scrutiny: Transgressing the Non-Confiscation Taxation Principle? - Rodrigo Rohrhirsch, Lucía (2020)
One of the principles that limit the State’s taxing power is the principle of non-confiscation. In 2019, the Constitutional Court analyzed the scope of the aforementioned principle in a judgment that dismissed a constitutional action filed by a mining company that requested the non- application of Supreme Decree No. 130-2013-PCM, for breaching the principles of non-confiscation, legality and matter for loi. In this paper, the author analyses whether the Regulation Contribution in favor of the OEFA violates the principle of non-confiscation and for this purpose, she explains the types of taxes that are regulated in the Peruvian legal system and which is the legal treatment that has been established for each type. In addition, she briefly makes some comments with regard to the Constitutional Court’s judgment.